A Global view of the Eclipse over the Earth (GEE) in 2009 and 2012. (5th March 2015) - Handa, T.; Hata, K.; Hara, T.; Horaguchi, T.; Hiramatsu, M.; Arai, T.; Sato, Y.; Ohnishi, K.
Abstract : A solar eclipse is one of the most popular events in astronomy. Although it is the single astronomical event, it gives different images from place to place and changes in time. It is the most important message from astronomy to the public that an apparent face depends on the viewpoint and we should get the comprehensive view.